Comparing Clock Test for Cognitive Screening: Quantitative Analysis of Five Scoring Methods – What Is Optimal? - Gea Pandhita; Bambang Sutrisna; Samekto Wibowo (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2020)
Objectives: The clock drawing test (CDT) is a widely used cognitive screening tool that has been well accepted. However, it is still questionable which scoring system is the best. We assessed the correlation of five common scoring methods of the CDT with Mini Mental State Examination (MMSE), and intercorrelations between each different scoring system. Methods: CDT scores of different scoring systems from participants from the geriatric club in Pondok Kopi Jakarta Islamic Hospital, were compared. The CDT was scored according to the methods of Rouleau, Babins, Mendez, Lin, and Shulman. Correlation coefficients between the five scoring methods of the CDT with MMSE were calculated, as well as the intercorrelations between each different scoring system. Results: The study sample consisted of 106 non-demented subjects, aged between 60 and 77 years. The five scoring methods of the CDT correlated significantly with MMSE, but correlation coefficients were moderate (r = 0.43 to r = 0.46). The highest was Lin's method (r = 0.46). Especially, correlation coefficients between the five scoring methods of the CDT with MMSE attention domain were higher (r = 0.42 to r = 0.52). The intercorrelations between each different scoring system were high (r = 0.87 to r = 0.99). The correlation coefficients between Rouleau's method with Mendez's method was the highest (r = 0.99). Conclusions: The correlation of five common scoring methods of the CDT with MMSE were moderate positive. The CDT scored according to the method of Lin was the highest. The intercorrelations between each different scoring system were high.